34.7k views
5 votes
Find the following expression by multiplying
(A+b)^3

User Ernad
by
5.6k points

2 Answers

0 votes

Answer:


a^3 + 3a^2b + 3ab^2 + b^3

Explanation:

Hope This Helps :)

User Cumul
by
6.4k points
4 votes

Given expression: (A+b)^3.

We can expand it into three factors as (A+b)(A+b)(A+b).

First we would foil (A+b)(A+b) =
A^2 + Ab+Ab+ b^2

Combining like terms, we get

=
A^2 +2Ab + b^2

Now, we would multiply (A^2 +2Ab + b^2) and (A+b).

=
A^3 + A^2b + 2A^2b+2Ab^2 + Ab^2+ b^3

Combining like terms, we get


=A^3+3A^2b+3Ab^2+b^3

Therefore,


\left(A+b\right)^3=\quad A^3+3A^2b+3Ab^2+b^3


User David Koelle
by
6.2k points